Highway safety manual, 1st edition. Supplement 2014 : includes chapter 18, chapter 19, and appendix B to part C - Bonneson, James A.; Texas A & M Transportation Institute; American Association of State Highway and Transportation Officials; National Cooperative Highway Research Program (©2014., 2014)
'The Highway Safety Manual Supplement includes two new chapters that help utilize the predictive method to estimate the expected average crash frequency (in total, by crash type, or by crash severity) for both freeways and ramps with known characteristics. The third chapter, Appendix B for Part C, describes two specialized procedures to be used with the predictive method presented in the new Chapters 18 and 19; the first procedure is used to calibrate the predictive models; the second, the Empirical Bayes Method, helps combine observed crash frequencies with the estimates provided by the predictive models.'-- Publisher's website.
ch. 18. Predictive method for freeways -- ch. 19 Predictive method for ramps -- Appendix B: Specialized Procedures Common to Chapters 18 and 19.
'Publication Code: HSM-1S'
'Under National Cooperative Highway Research Program Project 17-45, the Texas A&M Transportation Institute (James A. Bonneson, Principal Investigator) performed research to develop the models and information in this supplement and prepared the text of these chapters.' -- Preface.
Includes bibliographical references (p. B-30).
Keywords: Traffic safety -- United States -- Handbooks, manuals, etc; Roads -- United States -- Safety measures -- Handbooks, manuals, etc